Perspektywy zmian bazy ekonomicznej Dolnego Śląska w świetle usieciowienia - Miszczak, Katarzyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The main aim of this article is determination of prospects of changes of Lower Silesia's economic base in networking aspect. Researching structure of this region's economic base it was used index of localization (Florence's ratio) and characterized egsogenous sector for territorial units of NTS 3 grade - subregions and NTS 4 grade - administrative districts.Carried researches and observation of hitherto phenomenons existing on Lower Silesia's area have allowed to ascertain, that presently obtaining of advantageous competitive position by some subject is possible on the assumption that extension and diversification of settlement unit's export base, heading for modernizing its egsogenous sector, is possible to achievement in contemporary realities only due to functioning compound collocation of each grade's net coherences.As a reason of the elaboration's limited volume presented matters, opinions and conclusions were depicted in synthetic form. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 96-105